THE DEFINITION OF FUNCTIONAL DETERIORATION OF RAILWAY ROLLING STOCK - Gnennyi, O. M. (Science and Transport Progress, 2007)
In the article substantiated necessity to determine functional depreciation of railroad cars in the correlation with locomotives. The functional depreciation determine comparison net present value of the cash flows from using of the appraisal object and from using the analogue object. The factors affecting to the functional depreciation is determined.